The moderating impact of maturation on locomotor performance responses and bilateral asymmetries to 11-week differential learning plyometric training in youth basketball players - Arede, J.; Ayala, F.; Gonzalo-Skok, O.; Angulo, F.; Aguiar, R.; Schöllhorn, W. (International Journal of Sports Science & Coaching, 2025)
This study sought to examine the impact of a differential plyometric training (DL-PT) programme on measures of locomotor performance and bilateral asymmetries, while also assessing whether post-training responses were influenced by maturation. Thirty-three male youth basketball players from the same basketball club academy completed this study. All participants were tested before and after an 11-week DL-PT programme of 10 m sprint time, jump height (i.e., unilateral and bilateral countermovement jumps [CMJ]), and change of direction performance (Modified 505 agility test). The DL-PT programme was integrated into their regular basketball training routine and consisted of three sets of five jumps with 20 s of passive recovery between jumps and two minutes between sets, performed twice per week. Subjects were verbally instructed to execute different added fluctuations before each repetition. Bayesian inference was used to explore differences between pre-and post DL-PT programme on players` locomotor performance. A moderation model was conducted to analyze interactions of maturation as a continuous variable on the dependent variables. The results demonstrated statistically significant post-intervention improvements in locomotor performance measures, including bilateral and unilateral CMJ heights and change of direction (COD) times. Moderation analysis revealed significant interactions between maturity status (%PAH) and certain locomotor performance outcomes. Less mature individuals showed lower improvements in unilateral CMJ height but greater improvements in 180° COD time. Tentatively, the main findings of this study suggest that maturational developments in the neuromuscular system offer some mechanistic explanation for the varied dose responses observed after the 11-week DL-PT programme.